Mediastinal Desmoid Tumor With Remarkably Rapid Growth: A Case Report. Issue 52 (December 2015) - Lee, Joon Hyung; Jeong, Jae Seok; Kim, So Ri; Jin, Gong Yong; Chung, Myoung Ja; Kuh, Ja Hong; Lee, Yong Chul
Abstract : Abstract: Desmoid tumors (DTs) are a group of rare and benign soft tissue tumors that result from monoclonal proliferation of well-differentiated fibroblasts. Since DTs tend to infiltrate and compress adjacent structures, the location of DTs is one of the most crucial factors for determining the severity of the disease. Furthermore, DTs can further complicate the clinical course of patients when the growth is remarkably rapid, especially for DTs occurring in anatomically critical compartments, including the thoracic cavity. The authors report a case of a 71-year-old man with a known mediastinal mass incidentally detected 4 months ago, presenting dyspnea with right-sided atelectasis and massive pleural effusion. Imaging studies revealed a 16.4 × 9.4-cm fibrous mass with high glucose metabolism in the anterior mediastinum. The mass infiltrated into the chest wall and also displaced the mediastinum contralaterally. Interestingly, the tumor had an extremely rapid doubling time of 31.3 days. En bloc resection of the tumor was performed as a curative as well as a diagnostic measure. Histopathologic examination showed spindle cells with low cellularity and high collagen deposition in the stroma. Immunohistochemical staining was positive for nuclear β-catenin. Based on these pathologic findings, the mass was diagnosed as DT. After surgery, there has been no evidence of recurrence of disease in the patient. This patient presents a mediastinal DT with extremely rapid growth. Notably, the doubling time of DT in our case was the shortest among reported cases of DT. Our experience also highlights the benefits of early interventional strategy, especially for rapidly growing DTs in the thoracic cavity.